Caregivers’ concerns and experiences with their childs’ peri-operative care when undergoing cardiac surgery - Kielty, Patrick (My University, 2022)
Objective: To identify and explore experiences and concerns of caregivers whose children underwent anaesthesia for cardiac surgery. Design: A descriptive, exploratory, qualitative study was undertaken. Setting: The study was conducted at Nelson Mandela Children’s Hospital, Johannesburg South Africa. Subjects: A total of 13 caregivers of children who were undergoing cardiac surgery were interviewed between June 2020 and September 2020. The sample size required by this type of study was determined by the scope, depth, and nature of the information that was required to gain insight into the experiences of the participants Interventions: None. Measurements and main results: Semi-structured, open-ended interviews were conducted with the aid of an interview guide. Caregivers were interviewed in either English or isiZulu. Field notes and audio recordings were collected. Data were coded and thematically analysed. The caregivers reported their experiences to be complex and their common experiences and concerns included being fully informed, feeling disempowered and excluded which led to feelings of anxiety, fear and guilt. However, caregivers reported feeling hope and perceived that they were welcomed and valued by supportive staff. Caregivers reported having good relations with, as well as having a good understanding of the role of the treating anaesthetist. Conclusion: Numerous complex, interacting factors were identified that influenced the perceptions and experience of the caregivers. Education of the caregiver prior to surgery, employing a family-centred multidisciplinary approach, should be implemented by the healthcare workers. This could help create confidence in the anaesthetist and may improve the overall experience of families of children undergoing cardiac surgery.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Medicine in Anaesthesiology to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, 2022